2013
DOI: 10.1111/hcre.12017
|View full text |Cite
|
Sign up to set email alerts
|

The Reference Frame Effect: An Intergroup Perspective on Language Attitudes

Abstract: Invoking self‐categorization and social identity theories, this study predicted that ingroups would be evaluated more favorably than outgroups, but that ingroup membership would change as a function of reference frame. Using the matched‐guise technique, moderate and broad American Southern English accented guises were presented to Californian listeners (N = 175). These were paired either with a Californian‐accented (interregional reference frame) or Punjabi‐accented English speaker (international reference fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 45 publications
1
24
0
1
Order By: Relevance
“…Third, the two varieties are associated with distinct stereotypes. Previous research has specifically shown that American listeners tend to attribute less status and solidarity to PE than SAE speakers (e.g., Dragojevic & Giles, ). Expecting to replicate these latter findings pertaining to accent and stereotypes, we predicted that:
H1a‐b: The SAE speaker will be rated more favorably on (a) status and (b) solidarity traits than the PE speaker.
…”
Section: Methodsmentioning
confidence: 99%
“…Third, the two varieties are associated with distinct stereotypes. Previous research has specifically shown that American listeners tend to attribute less status and solidarity to PE than SAE speakers (e.g., Dragojevic & Giles, ). Expecting to replicate these latter findings pertaining to accent and stereotypes, we predicted that:
H1a‐b: The SAE speaker will be rated more favorably on (a) status and (b) solidarity traits than the PE speaker.
…”
Section: Methodsmentioning
confidence: 99%
“…The Punjabi accent was selected for a number of reasons. First, past research has shown that American listeners can reliably identify this variety (as Indian) solely from differences in pronunciation (Dragojevic & Giles, 2014). Second, many Americans frequently encounter Punjabi-accented speakers in their everyday lives (Chand, 2009).…”
Section: Studymentioning
confidence: 99%
“…Second, many Americans frequently encounter Punjabi-accented speakers in their everyday lives (Chand, 2009). Third, past research has shown that the Punjabi accent tends to be negatively stereotyped in the U.S.A. on both status and solidarity traits relative to SAE (Dragojevic & Giles, 2014;Lindemann, 2005).…”
Section: Studymentioning
confidence: 99%
“…A high degree of consistency has been found from the data collected in these studies. More specifically, it has been widely demonstrated that speakers of standard language varieties are usually rated more positively in terms of status when compared to speakers of forms deemed non-standard (see Dragojevic and Giles 2014;Edwards 2011;McKenzie, Kitikanan, and Boriboon 2016). In the case of England, for instance, researchers have demonstrated that English nationals, historically, tend to evaluate standard varieties associated with English speakers from the south of England, such as Received Pronunciation (RP) and Standard Southern British English (SSBE), more favourably in comparison with those speakers of linguistic forms of English perceived to be non-standard and, most particularly, with regards to the English of speakers from urban areas in the north of England, e.g., in Liverpool and Newcastle (Garrett 2010;Giles 1970).…”
Section: Language Attitudesmentioning
confidence: 99%